2022
DOI: 10.3390/vaccines10121994
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Influenza Vaccination and Its Determinants during 2020–2021 Flu Seasons in China: A Cross-Sectional Survey

Abstract: Young children aged 6–59 months are recommended as one of the priority groups for seasonal influenza vaccination in China. This study assessed influenza vaccination coverage and the factors associated with vaccination uptake among children in three Chinese provinces. In September 2021, 2081 caregivers with children <5 years completed self-administered questionnaires as part of a cross-sectional survey. Logistic regression was used to assess determinants of childhood influenza vaccination. A total of 43.63% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…A total of 36 studies published from 2004 to 2023 were finally analysed and summarised [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] ( Table 1 ). Most of the studies were performed in Asia ( n = 15, 42%) and the Americas ( n = 14, 39%), followed by Europe ( n = 5, 14%) and Oceania ( n = 2, 6%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 36 studies published from 2004 to 2023 were finally analysed and summarised [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] ( Table 1 ). Most of the studies were performed in Asia ( n = 15, 42%) and the Americas ( n = 14, 39%), followed by Europe ( n = 5, 14%) and Oceania ( n = 2, 6%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies reported on the factors associated with SIV (uptake in the last flu season, uptake in lifetime, acceptance/hesitancy), as shown in Table 2 . Parental education level was a strong predictor reported in nine studies, with one study reporting a negative association [ 44 ] and some reporting a positive association with acceptance and uptake [ 19 , 20 , 37 , 38 , 40 , 45 , 50 ]. Household income [ 14 , 36 , 37 , 38 , 40 , 41 , 44 , 50 ] and having chronic diseases/comorbidities [ 35 , 36 , 41 , 47 , 48 , 51 , 52 ] were also important predictors of vaccine acceptance and uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Our study revealed that the vaccination rate among children (35.68%)was significantly higher than that among the other groups. 14 Although children aged 6–59 months are recommended as one of the key groups for seasonal influenza vaccination in China, 15 the vaccination rate of children in China is much lower than that of children in other regions in the world. For example, the VCR of children aged 5–12 years and under 5 years in the U.S. was approximately 52.6% in 2017, 16 and that in Japan was 50.6% in 2012–2013.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal influenza vaccine serves as a key preventive measure against influenza and its associated complications, offering numerous benefits, such as protection against influenza infection, hospitalization, and disease severity [ 10 – 18 ]. The Centers for Disease Control and Prevention recommends that all individuals aged 6 months or older receive the vaccine annually, with a higher priority assigned to high-risk groups and healthcare workers [ 19 – 23 ].…”
Section: Introductionmentioning
confidence: 99%